2017
DOI: 10.3892/or.2017.5740
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-605 functions as a tumor suppressor by targeting INPP4B in melanoma

Abstract: MicroRNAs (miRNAs) play crucial roles in the initiation and progression of various cancers, including melanoma. Recently, the genetic variants and deregulation of miR-605 have been reported to participate in carcinogenesis. However, the expression status of the miR-605 in melanoma tissues and its role in melanoma progression remain unknown. In this study, we found that miR-605 was significantly downregulated in melanoma cell lines and clinical specimens. Further function studies demonstrated that miR-605 suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…One group has carefully shown that miR-605-5p promotes the P53 stress response and inhibits apoptosis in colorectal carcinoma cells [ 118 ]. Another report recently showed evidence that miR-605-5p acts as a tumor suppressor in melanoma by inhibiting INPP4B [ 119 ]. Future studies will explore whether there a CNS-specific role for miR-605-5p exists.…”
Section: Discussionmentioning
confidence: 99%
“…One group has carefully shown that miR-605-5p promotes the P53 stress response and inhibits apoptosis in colorectal carcinoma cells [ 118 ]. Another report recently showed evidence that miR-605-5p acts as a tumor suppressor in melanoma by inhibiting INPP4B [ 119 ]. Future studies will explore whether there a CNS-specific role for miR-605-5p exists.…”
Section: Discussionmentioning
confidence: 99%
“…SGK3 has been found in others cancers as a carcinogenic gene [ 42 , 52 55 ]. A recent report revealed that SGK3 plays a vital role in glioblastoma as the target gene of miR-212-3p [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-605 inhibits the progression of intrahepatic cholangiocarcinoma by suppressing gankyrin ( 34 ). miR-605 also functions as a tumor suppressor in melanoma by regulating the expression of inositol polyphosphate-4-phosphatase type II B ( 35 ). In addition, miR-605 was also demonstrated to affect the proliferation, migration and invasion of non-small cell lung cancer, prostate cancer, and breast cancer ( 18 , 19 , 36 ).…”
Section: Discussionmentioning
confidence: 99%